Tinjauan Sains dan Agama terhadap Vaksin SARS-Cov-2 : Sebuah Pendekatan Analisis Rasch - Albertos Damni; Dinyah Rizki Yanti Zebua; Bali Yana Fitri (Symbiotic: Journal of Biological Education and Science, 2022)
Science and Religion are two entities that often clash. The purpose of this study is to interpret the tendencies of the students of the two entities by using the Rasch analysis approach to re-validate the previous scale. Science students are Biology Education Department and religion are Islamic Education Department. This study shows a significant difference between Science and Religion students in giving approval to the Corona-SARS-Cov-2 virus vaccine.